Educating Independence in Civic Education at SDN 2 Beji, Banyumas, Using the Independent Curriculum - Husen, Solikhati Nabilah; Wakhudin, Wakhudin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the process of independent character education in Civic Education learning in Class V of SDN 2 Beji, Banyumas using the Merdeka Curriculum. The learning process is carried out in an integrative thematic manner, where learning combines various subjects in one theme, so that students can learn holistically and textually. This study uses a descriptive qualitative approach with a phenomenological method. The main data sources come from interviews with Class V teachers, observations of Class V Civic Education learning, and interviews with Class V students, teachers, and principals, as well as documentation studies. The results of the study show that teaching independent character through Civic Education using the Merdeka Curriculum gives students the freedom to determine how to behave, process, think, and act creatively in order to develop each individual by determining their own destiny.